The 5 forces of change: a blueprint for leading successful change - Greenfield, Anthony (Henry Stewart Talks, 2010)
The problem with change, People and change, How do people respond to major change?, The 5 forces of change, Certainty, Purpose, Control, Connection, Success
Reviewed at 2017/10/31